Introducing the negotiation navigation map - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2009)
In this article we reflect upon negotiation strategies and explore the utility of reconciling the dichotomy between interest-based and positional approaches to negotiation. Ultimately, we advocate for a ‘constructive model’ of negotiation and introduce the ‘negotiation navigation map’ that serves the negotiator well in preparing for this approach to negotiation.